2018
DOI: 10.1177/0300060518781253
|View full text |Cite
|
Sign up to set email alerts
|

Prompt admission to intensive care is associated with improved survival in patients with severe sepsis and/or septic shock

Abstract: ObjectiveTo investigate the association between time from hospital admission to intensive care unit (ICU) admission (door to ICU time) and hospital mortality in patients with sepsis.MethodsThis retrospective observational study included routinely collected healthcare data from patients with sepsis. The primary endpoint was hospital mortality, defined as the survival status at hospital discharge. Door to ICU time was calculated and included in a multivariable model to investigate its association with mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…951 This is more limited with regard to sepsis, but a report has indicated that every hour of delay from hospital visit to ICU admission in severe septic/septic shock increased the adjusted odds ratio of the mortality rate by 1.11 (95%CI: 1.01 to 1.02). 966 …”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%
See 1 more Smart Citation
“…951 This is more limited with regard to sepsis, but a report has indicated that every hour of delay from hospital visit to ICU admission in severe septic/septic shock increased the adjusted odds ratio of the mortality rate by 1.11 (95%CI: 1.01 to 1.02). 966 …”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%
“…RCTs are virtually impossible in this field, and a consensus was reached with the current evidence that critically ill patients should be managed at the ICU even in the Admission, Discharge, and Triage Guidelines 951 . This is more limited with regard to sepsis, but a report has indicated that every hour of delay from hospital visit to ICU admission in severe septic/septic shock increased the adjusted odds ratio of the mortality rate by 1.11 (95%CI: 1.01 to 1.02) 966 …”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%
“…RCTs are virtually impossible in this field, and a consensus was reached with the current evidence that critically ill patients should be managed at the ICU even in the Admission, Discharge, and Triage Guidelines [ 989 ]. This is more limited with regard to sepsis, but a report has indicated that every hour of delay from hospital visit to ICU admission in severe septic/septic shock increased the adjusted odds ratio of the mortality rate by 1.11 (95%CI: 1.01 to 1.02) [ 1004 ].…”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%
“…3,5 Identifying the severity of disease and likelihood of further deterioration of surgical sepsis patients with high accuracy and rapid turnaround remains a critical unmet need for hospitalized patients, since time to intervention and antimicrobial treatment is a critical determinant of outcome. 6,7 Current in-hospital early warning systems for sepsis (Modified Early Warning System [MEWS]) are used to alert health-care providers to the possibility of sepsis. 8 In many cases, the decision to initiate sepsis resuscitation bundles and more intensive management is an empiric decision made by the health-care provider at the bedside, prior to documentary evidence of microbial infection, organ injury or immunological dyscrasia.…”
Section: Introductionmentioning
confidence: 99%